What do mountaineers and their guides in Serbia know about venomous snakes? A pilot questionnaire analysis - Nikolić, Sonja; Radonjić, Isidora; Miloradović, Zorana (Turizam, 2022)
More and more people go/return to nature seeking recreation, relaxation, stress/anxiety relief, socializing with like-minded persons, etc. Not all of them know what they can stumble upon walking through various terrains. We wanted to check how much do hikers/mountaineers and those who took a course for excursion and hiking guides know about venomous snakes present in Serbia and the basic first aid in the case of a bite. For this purpose, we designed a questionnaire containing 20 simple questions that addressed recognition, ecology, distribution, the basics of venomous snakes’ conservation, first-aid measures, and people’s feelings regarding these reptiles. Results suggest that our target group is agreeably well informed given the amount and quality of easily accessible data for Serbia. However, some misconceptions were detected that must be corrected. There are indications of the increase in mountain/adventure tourism in Serbia, which is partially conditioned by the COVID-19 pandemic. Therefore, we must invest additional effort in examining and educating both mountaineers and “plain” tourists so both the people and snakes would stay safe. To achieve this long-term goal, we should exchange knowledge and experiences with experts from various fields, i.e. biology, medicine, tourism, economics, geography, etc.